Changes in Factor VIII Complex Activities During the Production of a Clinical Intermediate Purity Factor VIII Concentrate - Prowse, C V; Griffin, B; Pepper, D S; Dickson, A J; McQuillan, T A; Dickson, I H; Foster, P R (Thrombosis and Haemostasis, 1981)
Samples taken at various stages of preparation of intermediate purity factor VIII concentrate were assayed for factor VIII coagulant activity (VIII:C), factor VIII coagulant antigen (VIIIC: Ag) and factor VIII related antigen (VIIIR: Ag). The antigen results were used to assess mechanical loss during fractionation as these markers are relatively stable. In contrast VIII:C is sensitive to both mechanical and inactivation losses.The major loss of factor VIII occurred during the cryoprecipitation and extraction step and was due to both mechanical loss and inactivation. Losses before and after this step were largely due to inactivation of the factor VIII.Assay of VIIIR: Ag in concentrates presented problems and a modified technique is suggested.
Keywords: Factor VIII Concentrates; Plasma fractionation